Pembentukan Karakter Manusi Dalam Filsafat Pendidikan Islam - Fitrian Nurazizah; Saiful Anwar (Akademika: Jurnal Keagamaan dan Pendidikan, 2024)
The purpose of writing this article is to find out what character education is like at MSU Nashrus Sunnah and the efforts made to build it, as well as how it is related to the philosophy of Islamic education. The research method we have determined is qualitative data collection, namely observation and in-depth interviews in educational development efforts based on Islamic educational philosophy. Then the author analyzes and describes both. According to research conducted, the development of human character, especially in school learning, is very important and a boost in improving human character is collaboration between educators, students and parents. Without the collaboration of three key elements, it is impossible to create human character guided by Islamic teachings